Sosialisasi Radiasi Telepon Seluler dan Fenomena Vampir Energi di Desa Perampuan, Labuapi, Lombok Barat - Sudi Mariyanto Al Sasongko; A.B Muljono; I.M Ari Nrartha; I.M Ginarsa; S. Sultan (JURNAL KARYA PENGABDIAN, 2020)
Handphone produce electromagnetic fields of varying magnitude. SAR (Specific Absortion Radiation) and power density affect radiation exposure. WHO set the SAR radiation limit to be 1.6 W/Kg and the power density limit was 4.5 watts/m2 for the 900 MHz, and 9 watts/m2 for the frequency 1800 MHz. SAR values that exceed the threshold can cause physiological and psychological effects on humans. Electronic equipment connected to electrical installations still absorbs energy even though it inactive and termed vampire energy. The PKM team's measurements of the energy vampire of household electrical appliances range from 0.1 watts to 8.3 watts. The socialization activities on cellular phone radiation and energy vampires carried out in Perampuan Village is for sharing knowledge. The method used: presentation, electrical installation demonstration and measurement of energy vampires. The enthusiasm of the participants was quite high and hoped that there were regular activities for themes related to the electrical field.